Notalgia paresthetica: a review for dermatologists. (15th December 2017) - Howard, Matthew; Sahhar, Lukas; Andrews, Frank; Bergman, Ralph; Gin, Douglas
Abstract: Notalgia paresthetica (NP) is an underdiagnosed condition that presents with unilateral pruritus medial to the scapula on the midback with or without an associated hyperpigmented or hypopigmented macule. There is a paucity of recent reviews on this chronic cutaneous neuropathy in peer‐reviewed journals. Current theories propose the condition is likely multifactorial, including spinal entrapment and muscular compressive neuropathy. An extensive literature review was performed by searching the MEDLINE database to review all published works on notalgia paresthetica. This review will provide a useful update for clinicians on the pathogenesis, clinical features, biopsy features, risk factors, and management options for this condition including pharmacological and nonpharmacological methods detailing published treatment options to date for this difficult to treat condition.